Reserve Potential Sandy Clay as a Raw Materials Cement Village Hambalang, County Citeureup District Bogor Province Jawabarat – Indonesia - Syahrulyati, Teti; Irianto, Singgih; Suhendi, Yusup (International Journal of Engineering and Technology, 2018)
Administratively the research area is in Hambalang Village Kec. Citeureup Kab. Bogor West Java, travel time to the location of the city of Bogor for 60 minutes by motor vehicle, the area of research around 1732 ha. The existence of sedimentary rocks in the form of limestones and batulempung is utilized by one cement factory in Indonesia as raw material of cement. Measurement and sampling is done to know the amount of measured reserves. Analysis of the content of oxide compounds is done by AAS method to determine the levels of the compounds they contain. The results of the calculations of SiO2 and Al2O3 are abbreviated as (AI = alumina Index) and the pattern of distribution is made with the aim that the mining process becomes effective, efficient and directed. The method use to principle of the concept of three-point method is used as the basis for making contours of the distribution of compounds contained. Drilling data, chemical analysis, DTM (Digital Terain Modeling) data and Isoline data generated were obtained using Autoclan 3D map 2015 and Autoplan Geomo. The calculation of reserves (AI / Alumina Indek 3.21 - 3.70%) with the highest reserves 1,643,814 Tones. The smallest reserve (AI quality 5.00 - 6.01%) is 199,980 Tones. This research resulted in a map of the distribution of Alumina index, so as to facilitate the extraction and very helpful in executing the area / block that must be mined.Â Â